Fabrication and characterisation of micro- and nano- structures with high aspect ratio - McCarthy, Joseph (Trinity College (Dublin, Ireland). School of Chemistry, 2011)
The main aim of the work presented in this thesis was to develop novel high aspect ratio micro- and nano- structures by using metal alkoxide derived sol-gels and polymer solutions and infiltrating them into porous templates. These structures are expected to find a range of potential biomedical, photonic and photocatalytic applications. Chapter 1 covers the introduction to properties of the various materials and describes main synthetic approaches used throughout the work.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.